2021
DOI: 10.33963/kp.15673
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of left atrial overload in obese and nonobese patients with atrial fibrillation qualified for electrical cardioversion

Abstract: Background Biomarkers of left atrial (LA) overload are considered factors affecting the efficacy of atrial fibrillation (AF) treatment. Increasing obesity rates contribute to a growing number of obese patients qualified for electrical cardioversion (CVE). aims The aim of the study was to evaluate serum concentrations of biomarkers of LA overload and their impact on the efficacy of CVE. methods A total of 82 patients with persistent AF who underwent successful CVE were prospectively enrolled in the study. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Gürses KM et al (2019) [98] reported that pre-cardioversion Gal-3 levels in persistent AF corresponded to a higher left atrial volume index and were associated with early AF recurrence following successful sinus rhythm restoration. In contrast, Cicho ń M et al (2021) [101] did not find any link between circulating Gal-3 levels and the risk of recurrent AF in obese and non-obese patients with persistent AF. The same results were obtained in another study involving 75 non-HF patients with paroxysmal or persistent AF referred for electrical cardioversion [102].…”
Section: Galectin-3mentioning
confidence: 84%
See 2 more Smart Citations
“…Gürses KM et al (2019) [98] reported that pre-cardioversion Gal-3 levels in persistent AF corresponded to a higher left atrial volume index and were associated with early AF recurrence following successful sinus rhythm restoration. In contrast, Cicho ń M et al (2021) [101] did not find any link between circulating Gal-3 levels and the risk of recurrent AF in obese and non-obese patients with persistent AF. The same results were obtained in another study involving 75 non-HF patients with paroxysmal or persistent AF referred for electrical cardioversion [102].…”
Section: Galectin-3mentioning
confidence: 84%
“…Clinical evidence for the discriminative value of GDF15 for AF relapse or sinus rhythm maintenance is extremely limited. There is one small study that prospectively included 82 patients with persistent AF [101]. Although log10 serum GDF-15 levels correlated positively with the CHA2DS2-VASc score, there was no close association between GDF-15 levels and sinus rhythm maintenance in patients after successful electric cardioversion [101].…”
Section: Gdf15mentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular risk factors (i.e., hypertension, obesity or sleep apnoea) may contribute to the development of AF [ 34 , 35 ]. The CARDIO-FIT study showed that cardiorespiratory fitness predicts the recurrence of arrhythmia in obese patients with symptomatic AF [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient targeting may important to maximize the chance of detecting AF, which is a difficult balance between the possibility to maximize sensitivity and the problems linked to managing a large number of subjects. A series of criteria for patient targeting can be applied, including age, CHA 2 DS 2 --VASc, or CHA 2 DS 2 -VA [5], but also biomarkers such as brain natriuretic peptide (BNP) or N-terminal pro-BNP peptide (NT-proBNP) [4,10,11]. We think that the large amount of data collected in NOMED-AF deserves further analysis to assess the potential for specific targeting of candidates to AF screening based on clinical criteria (age, CHA 2 DS 2 -VASc) or biomarkers (NT-proBNP was measured in the study to assess the possibilities to maximize the feasibility of screening programs in daily practice) [5].…”
mentioning
confidence: 99%